1970
DOI: 10.3329/jdmc.v18i1.6300
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Causes and Management of Retained Placenta of Admitted Cases in In-Patient Department of Dhaka Medical College Hospital

Abstract: Retained placenta is a condition in which the placenta is retained for more than half-an hour after the birth of a child. It accounts for 5-10% of all postpartum haemorrhage (PPH). The present study was conducted to find out the incidence, causes and management of retained placenta of admitted cases in In-Patient Department (IPD) of Obstetrics & Gynaecology of Dhaka Medical College Hospital, Dhaka during the period from June 01 to December 31, 2003. 163 patients were included in the study who presented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…About the per vaginal examination in this present series it was observed that moderate per vaginal bleeding was in 85.0%, vaginal full with clot was in 82.0% and OS was open in 92.0%. In Das [16] study showed the dilatations of the cervical during paravaginal examination, 92.0% cases were open and in 8.0% cases closed. Time interval between delivery and removal of placenta in an important factor.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…About the per vaginal examination in this present series it was observed that moderate per vaginal bleeding was in 85.0%, vaginal full with clot was in 82.0% and OS was open in 92.0%. In Das [16] study showed the dilatations of the cervical during paravaginal examination, 92.0% cases were open and in 8.0% cases closed. Time interval between delivery and removal of placenta in an important factor.…”
Section: Discussionmentioning
confidence: 92%
“…The previously mentioned study in Kasturba Hospital, India by Chhabra et al [2] showed a number of thirty-six (50.7%) women required general anesthesia for manual removal. Another study by A Tandberg et al [16] showed that the use of general anesthesia for manual removal of placenta decreased from 74% in 1990to 19% in 1994 due to increased use of spinal analgesia. Another study by A Tandberg et al [11] showed that out of total of 24,750 deliveries registered during the five-year study period, placenta was removed manually in 165 women (0.6%).…”
Section: Discussionmentioning
confidence: 99%